Recensão: THE LUSOPHONE WORLD: THE EVOLUTION OF PORTUGUESE NATIONAL NARRATIVES - SARAH ASHBY - Pedro Lopes de Almeida (Revista de Estudos Literários, 2017)
Recensão crítica de THE LUSOPHONE WORLD: THE EVOLUTION OF PORTUGUESE NATIONAL NARRATIVES. SARAH ASHBY. Brighton: Sussex Academic Press, 2017